The Effectiveness of Problem-Based Learning on Students’ Learning Outcomes in the Al-Qur’an Hadith Subject - Elok Riska Wardani; Nasrodin Nasrodin; M. Endy Fadlullah; Imam Mashuri (Ainara Journal (Jurnal Penelitian dan PKM Bidang Ilmu Pendidikan), 2026)
This study aims to examine the effectiveness of constructivism-based Problem Based Learning (PBL) in improving students’ cognitive learning outcomes in the Al-Qur’an Hadith subject. The research employed a quantitative approach using a quasi-experimental nonequivalent control group design. The sample consisted of 35 eleventh-grade students selected through total sampling, including 17 students in the control group and 18 in the experimental group. The instrument used was a multiple-choice test that had been validated and tested for reliability. The results showed that the posttest mean score of the experimental class (86.11) was higher than that of the control class (79.12). The N-Gain analysis indicated moderate improvement in both groups, with scores of 0.53 for the experimental group and 0.36 for the control group. The t-test revealed a significant difference between the two groups (p < 0.05), particularly in analysis (C4) and evaluation (C5) skills. These findings indicate that constructivism-based PBL can support the development of higher-order thinking skills in Al-Qur’an Hadith learning.